American Radicals How Nineteenth-Century Counterculture Shaped the Nation - Holly, Jackson (New York Crown, 2019)
On July 4, 1826, as Americans lit firecrackers to celebrate the country's fiftieth birthday, both John Adams and Thomas Jefferson were on their deathbeds. They would leave behind a groundbreaking political system and a growing economy--as well as the glaring inequalities that had undermined the American experiment from its beginning. The young nation had outlived the men who made it, but could it survive intensifying divisions over the very meaning of the land of the free?
Includes index